Impact of the Timing of Protective Stoma Reversal on Survival in Rectal Cancer Patients Undergoing Postoperative Adjuvant Chemotherapy: A Retrospective Single Center Study - Wang J; Lu X; Xu Y; Wu Y; Zhang T; Li J (Cancer Management and Research)
Jiwei Wang,* Xiaoyun Lu,* Yanan Xu, Yin Wu, Tao Zhang, Jianguo Li Department of General Surgery, Digestive Disease Hospital, Affiliated Hospital of Zunyi Medical University, Zunyi, Guizhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jianguo Li, Department of General Surgery, Digestive Disease Hospital, Affiliated Hospital of Zunyi Medical University, 149 Dalian Road, Huichuan District, Zunyi, Guizhou, People’s Republic of China, Tel +86-13017410630, Email jianguo_zmu@163.comBackground: Postoperative adjuvant chemotherapy used in patients with stage II/III rectal cancer, is usually administered for 3 to 6 months. However, the optimal timing of protective stoma reversal remains controversial. This study aimed to investigate the effect of stoma closure before or after adjuvant chemotherapy on survival and stoma-related complications.Methods: A retrospective analysis was conducted on 144 patients who underwent radical rectal cancer surgery, prophylactic ileostomy and adjuvant chemotherapy from June 2018 to June 2021. 104 had their stoma reversal before adjuvant chemotherapy completion (Before group) and 40 after adjuvant chemotherapy completion (After group).Results: There were no significant differences between the groups regarding demographics, clinical characteristics, perioperative complications, OS, or DFS. Pathologic T-stage [HR = 2.620 (1.291– 5.320), P = 0.008 vs HR = 2.793 (1.297– 6.017), P = 0.009] and N-stage [HR = 2.204 (1.168– 4.157), P = 0.015 vs HR = 2.068 (1.125– 3.789), P = 0.019] were identified as independent risk factors for OS and DFS. Stoma reversal after completing chemotherapy [OR = 39.979 (3.964– 403.188), P = 0.002] and comorbidity [OR = 33.395 (5.931– 188.033), P < 0.001] were independent risk factors for stoma-related complications. In high-risk stage III patients with T4 or N2, the 3-year OS rate was significantly lower in Before group than in After group (70.3% vs 92.6%, P = 0.01), as was the 3-year DFS rate (60.94% vs 74.07%, P = 0.02). Prolonged stoma duration [HR = 0.991 (0.982– 1.000), P = 0.048] was an OS protective factor. Stoma reversal after chemotherapy [HR = 0.370 (0.141– 0.972), P = 0.044] and cumulative 5-FU dosage [HR = 0.991 (0.985– 0.997), P = 0.003] were DFS protective factors.Conclusion: In high-risk stage III patients, delayed stoma reversal after adjuvant chemotherapy may improve survival, but it may also lead to more stoma-related complications.Keywords: rectal cancer, protective ileostomy, adjuvant chemotherapy, survival, stoma-related complications